Design of dustbin with compactor features for domestic uses - Ahmad Faridzuan Hakim (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Nowadays solid waste management become a big issue because the awareness the important of manage the waste right way still lack among malaysia citizen. There are many action taken by malaysia government to educate malaysia citizen about the important and the right way to manage waste based on waste management matrix. Hence proper method used to design and fabricate most suitable waste compactor to every malaysia household.